A Longitudinal Assessment of Cervical Inflammation and Immunity Associated with HIV-1 Infection, Hormonal Contraception, and Pregnancy - Morrison, Charles S. (AIDS Res Hum Retroviruses, 2018)
Hormonal contraception (HC), particularly injectable depot-medroxyprogesterone acetate (DMPA), has been associated with increased HIV acquisition and higher levels of cervical regulated upon activation, normal T-cell expressed, and secreted (RANTES), also associated with HIV seroconversion. Longitudinal changes in cervical immunity associated with DMPA and combined oral contraceptives (COCs) have not been studied. Cervical samples from 216 HIV seroconverters in Uganda and Zimbabwe with matched samples from 727 HIV-uninfected controls were collected at two quarterly visits before (t − 2, t − 1), at (t0), and two visits following (t + 1, t + 2) HIV seroconversion and corresponding visits for HIV-negative controls. We measured 10 biomarkers of inflammation and immunity and used generalized linear models to estimate and compare biomarker levels across HIV status, contraceptive, and pregnancy groups. Biomarkers remained relatively stable across visits for controls, while in HIV-infected women cervical immunity started to change before seroconversion with RANTES and BD-2 increased and secretory leukocyte protease inhibitor (SLPI) decreased at t − 1 and continued to change at t0 with ICAM-1 up and IL-8 down and with more biomarkers after seroconversion (IL-1β, IL-6, MIP-3α, VEGF, and IL-1RA down and IL-1RA:IL-1β ratio up). In multivariable analyses, seroconverters had higher BD-2 at t − 1, higher RANTES and lower SLPI from t − 1 through t + 2, and lower IL-8 and IL-1RA at and/or after seroconversion compared to nonseroconverters. Compared to non-HC users, DMPA users had higher RANTES at all visits and lower BD-2 at t − 2 through t0, while COC users and pregnant women had higher IL-8 and SLPI at all visits; COC users also had lower BD-2 preseroconversion; pregnant women had lower RANTES at t0 − t + 2. Longitudinal patterns of cervical immunity differ between HIV seroconverters and HIV-negative women; seroconverters demonstrate increased RANTES and decreased SLPI starting before and continuing postseroconversion. Furthermore, these patterns are differentially regulated by DMPA, COC, and pregnancy.